Analisis Pengaruh Iklan, Kemasan, Dan Harga Terhadap Minat Beli Konsumen Air Mineral Merek Le Minerale(Studi Empiris Pada Mahasiswa FEB UMS) - Alhani, Jihan, Drs. Wiyadi, MM.,Ph.D (2016)
This research was conducted at the University of Muhammadiyah Surakarta, which aims to analyze the influence of rent against interest Buy, analyze the effect of packaging on the Interests Buy. Analyzing the influence of price on the Interests Buy. This study uses the survey design, the research took samples from a population and using questionnaires. The samples used were 100 students at the University of Muhammadiyah Surakarta. Methods of data collection in this study used a questionnaire to students. The analytical tool used in the research is to test the instrument, the classical assumption test, data analysis (Multiple Linear Regression Analysis, t-test, F and coefficient of determination (R ²). The results of data analysis can be obtained influences of rent positively and significantly to the mineral water brand Interests Buy LE MINERAL There Packaging influence positively and significantly to the mineral water brand Interests Buy LE MINERAL And the influences of the price of the Interests Buy LE MINERAL mineral water. There is the influence of Advertising, Packaging and Pricing simultaneously towards Interests Buy LE MINERAL mineral water brand. Keywords: Advertising, Packaging, Price, Request Buy